ANALISIS TERHADAP FUNGSI HUMAS PT RECKITT BENCKISER INDONESIA CILEUNGSI FACTORY - Ihzani, Moulita Indi (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2022)
This study aims to explain the public relations function of PT Reckitt Benckiser Cileungsi Factory. This study used a qualitative descriptive method focusing on research, namely the activities of public relations staff in carrying out functions at PT. Reckitt Benckiser. This research uses the descriptive qualitative method. Data collection techniques used are interviews, observation and documentation. The results of the analysis show that the functions of public relations applied in the activities of the company PT Reckitt Benckiser are: (1.) Supporting management activities in achieving organizational goals; (2.) Fostering a harmonious relationship between the organization and the public, both external and internal public; (3.) Creating reciprocal two-way communication by disseminating information from the organization to the public and channelling public opinion to the organization; (4.) Serve the public and advise organizational leaders in the public interest.